Diversity of Agaricaceae (Basidiomycota: Agaricales) in Dharampur and Kaprada Taluka, Valsad District: A Taxonomic Study - Patel Hirali; Solanki Hitesh; Patel Dilip (International Journal of Fungi, 2024)
The fungal diversity of Dharampur and Kaprada Taluka in Valsad District, Gujarat, India, particularly within the Agaricaceae family, has been extensively studied. According to a standard reference text, the Agaricaceae contains 85 genera and 1340 species. Agaricaceae fungi, categorized as macrofungi, are prevalent in this region and are notably utilized by local tribal communities for culinary purposes due to their edibility. The life cycle of Agaricus is cyclic beginning with the inoculation and germination of spores. This is followed by mycelium and primordia growth, fruiting body generation, maturation and release of spores. During fieldwork, specimens of Agaricaceae fungi were systematically collected using knives and transported to the laboratory for taxonomic and morphological analysis. Taxonomic classification and morphological characterization were conducted using authoritative sources such as "Fungi of Temperate Europe Volume 1 and 2" by Laesse and Peterson (2019) and "Mushrooms: How to Recognise and Gather Wild Mushrooms and Other Fungi" by Laessøe (2013). A total of 45 distinct species belonging to the Agaricaceae family were identified in the study area, highlighting their diverse ecological niches including soil, dead leaves, cow dung, and decomposed organic matter. This research underscores the rich fungal biodiversity present in the region and provides valuable insights into the ecological roles and potential applications of Agaricaceae fungi within local ecosystems. The findings contribute significantly to our understanding of fungal diversity in this specific geographical area, emphasizing both the ecological importance and cultural relevance of these fungi to the communities that depend on them. Further research could explore their pharmacological potentials or their roles in nutrient cycling, thereby enriching our knowledge of these understudied yet ecologically significant organisms.
Keywords: Agaricaceae; Dharampur; Diversity; Kaparada; Mushrooms